2015
DOI: 10.1024/0301-1526/a000415
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch calcification is strongly associated with coronary artery calcification

Abstract: AAC is a strong and independent predictor of CAC. The discriminative performance of AAC is high in detecting patients with low- and high-risk CAC scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…In our study, we found a significant association between AAC and severe coronary calcification as defined by the SS algorithm. Several previous studies strongly and consistently support a significant, positive association between AAC on chest X-rays and CAC that is detected by computed tomography (CT) [7, 8]. Bannas et al evaluated the association between AAC on chest X-rays and CAC scores that were determined by CT, where the AAC extent was divided into the same four grades (0-3) as the present study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In our study, we found a significant association between AAC and severe coronary calcification as defined by the SS algorithm. Several previous studies strongly and consistently support a significant, positive association between AAC on chest X-rays and CAC that is detected by computed tomography (CT) [7, 8]. Bannas et al evaluated the association between AAC on chest X-rays and CAC scores that were determined by CT, where the AAC extent was divided into the same four grades (0-3) as the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, AAC can be detected readily and reproducibly using chest X-ray, which is a simple, inexpensive tool that is widely available for assessing hospitalized patients with chest pain. Several studies have reported that the presence of AAC could serve as an independent predictor of coronary artery calcium (CAC) presence, while the AAC extent was correlated with CAC scores [7, 8]. Furthermore, CAC has been demonstrated to provide incremental and independent power in predicting CAD severity [9, 10], suggesting that AAC might be a good predictor for CAD severity.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a strong and independent correlation was found between coronary artery calcification and AAC [22]. In addition, a strong correlation was reported between AAC and renal artery calcification, which is an important indicator of renal artery disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional radiography is a convenient and inexpensive tool for identifying calcium ions in blood vessels [21-23]. In the general population, aortic arch calcification (AAC) found in chest radiotherapy has been shown to be associated with cardiovascular mortality during long-term follow-up [24]. Recent studies have shown that high-grade calcification was associated with cardiovascular and all-cause mortality in patients with HD using plain chest radiography [25].…”
Section: Introductionmentioning
confidence: 99%